y=mx+b where "m" is the gradient <-- marmar i hope you are familiar with this equation.
so for 2y =2-2x, you agree that it can be written as 2y=-2x+2, and after you factorise/simplify(ie divide everything by 2) it will look like
y =-x+1
does this look familiar to the form y= mx+b, hence we may deduce that m= -1
if we then look at the options they offer for the SECOND one 1x -4 =-1y
do you agree that this is the same as writing 1y= -1x +4
thus "m" =-1 which is the SAME for 2y =2-2x
for the THIRD one, 2y -4 =x, you agree this is the same as
y =(x/2)+(4/2) where "m" = 1/2 which is NOT THE SAME for
2y =2-2x
for the FOURTH one, 2y -3 =2x, you agree this is the same as writing y=(2x/2) +(3/2), thus "m" =1 which is NOT THE SAME for 2y =2-2x
therefore, it is true for only the SECOND ONE. and because it is true for the SECOND ONE we may dismiss the FIRST ONE which is "None of them" as a possible answer.
so the final answer is the SECOND ONE.
i hope this makes sense